In Vitro Antibacterial and Antifungal Activity and Datura Innoxia Extracts - Shama, Adam IY; Abd-Kreem, YM; Fadowa, AA; Samar, RM; Sabahelkhier, MK (International Journal of Environment, 2014)
The aim of this study was evaluated the Antimicrobial Activity of extraction of Datura innoxia (Seeds, leaves and roots). Datura innoxia Seeds, leaves and roots were collected to examine their antimicrobial activity. Extracts of different parts of the plant were tested against standard microorganisms by using the agar- well diffusion method. Extracts of methanol, and aqueous of seeds, leaves and roots were prepared and tested against four types of bacteria namely: Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Proteus vulgaris and two types of fungi namely: Aspergillus niger and Candida albicans. The methanolic and aqueous extracts of leaves showed high activities against fungi (A. niger) and less effect on the all bacteria. The methanolic extracts of seeds showed high activities against all organisms except fungi (C. albicanas), while the aqueous extracts of seeds showed no activity on the bacteria. All organisms were examined against known standard antibiotics and then compare the results of plant extracts with standard antibiotics. The results indicated that the antibacterial drug is less active than the plant extracts, while the antifungal drugs are more active than the plant extracts. DOI: http://dx.doi.org/10.3126/ije.v3i3.11077 International Journal of Environment Vol.3(3) 2014: 173-185